INDUSTRY 4.0 IMPACTS REVERSE LOGISTICS - Velásquez Monroy, Xiomara Daniela
The increasing focus on sustainable development, the circular economy and stricter environmental regulations have required companies and organizations that make up supply chains to take responsibility for the entire life cycle of their products. This, in order to maximize the recovery of the remaining value of the products at the end of their use and useful life, through the economical and efficient design, operation, control, and maintenance of the reverse logistics flow of their products, from the customers to initial manufacturers and suppliers, with the support of collection and recycling logistics operations in order to preserve the value and usefulness of materials for as long as possible, generating significant gains in the value chain. However, traditional reverse logistics cannot cope with the requirements of modern supply chains and requires the implementation of disruptive Industry 4.0 technologies, which would make it more efficient, with cleaner redistribution processes, with sustainability goals. related to the circular economy. The disruptive technologies of Industry 4.0 lead to improvements in business sustainability and introduce important innovative solutions in reverse logistics.